2017
DOI: 10.1177/2192568217699383
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Age as a Risk Factor for 30-Day Postoperative Outcomes Following Elective Anterior Cervical Discectomy and Fusion

Abstract: Study Design:Retrospective analysis of prospectively collected data.Objective:Anterior cervical discectomy and fusion (ACDF) is one of the most commonly performed spinal procedures. Considering the high success and low complications rate of ACDF and high prevalence of age-related degeneration of the cervical spine, the rates of ACDF are expected to continually rise. The objective is to identify the association between patient age and 30-day postoperative outcomes following elective ACDF.Methods:The 2010-2014 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
0
31
2
Order By: Relevance
“…Increased age has been reported as a risk factor for extended LOS, hospital readmissions, and adverse events following ACDF. 14,16,20,[22][23][24]30 The average age in our extended LOS group was greater than 60 years of age, and the average age in our normal LOS group was 55 years old. Age 65 was independently associated with extended LOS; however, it was not associated with 90-day readmission rates.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Increased age has been reported as a risk factor for extended LOS, hospital readmissions, and adverse events following ACDF. 14,16,20,[22][23][24]30 The average age in our extended LOS group was greater than 60 years of age, and the average age in our normal LOS group was 55 years old. Age 65 was independently associated with extended LOS; however, it was not associated with 90-day readmission rates.…”
Section: Discussionmentioning
confidence: 79%
“…Risk factors previously associated with extended LOS or hospital readmissions include advanced age, gender, race, insurance status, medical comorbidities, preoperative opioid use, preoperative anemia, and multiple-level surgery. [13][14][15][16][17][18][19][20][21][22][23][24][25] The purpose of our study was to identify independent risk factors for extended LOS and 90-day readmission rates following ACDF surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There was one study which utilized the American College of Surgeons’ National Surgical Quality Improvement Program (ACS-NSQIP) database to analyze the complications after ACDF. It demonstrated that, by multivariate logistic regression, aging was associated with pulmonary complications, UTI, cardiac complication, and sepsis [ 32 ]. There was also another large cohort study that revealed similar findings for older patients undergoing ACDF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age has been shown to be associated increased risk of 30-day postoperative complications and also is an independent risk factor for increased morbidity and increased stay in hospital. [13141516] Males are more prone to develop cervical degenerative disc disease. [1718192021222324] Higher incidence of spondylosis changes in population with increasing age and in males was reported by Sasaki et al .…”
Section: Discussionmentioning
confidence: 99%